A Predominant Role of AtEDEM1 in Catalyzing a Rate-Limiting Demannosylation Step of an Arabidopsis Endoplasmic Reticulum-Associated Degradation Process - Zhang, Jianjun; Xia, Yang; Wang, Dinghe; Du, Yamin; Chen, Yongwu; Zhang, Congcong; Mao, Juan; Wang, Muyang; She, Yi-Min; Peng, Xinxiang; Liu, Li; Voglmeir, Josef; et al. (Frontiers in Plant Science, 2022)
Endoplasmic reticulum-associated degradation (ERAD) is a key cellular process for degrading misfolded proteins. It was well known that an asparagine (N)-linked glycan containing a free alpha1,6-mannose residue is a critical ERAD signal created by Homologous to alpha-mannosidase 1 (Htm1) in yeast and ER-Degradation Enhancing alpha-Mannosidase-like proteins (EDEMs) in mammals. An earlier study suggested that two Arabidopsis homologs of Htm1/EDEMs function redundantly in generating such a conserved N-glycan signal. Here we report that the Arabidopsis irb1 (reversal of bri1) mutants accumulate brassinosteroid-insensitive 1-5 (bri1-5), an ER-retained mutant variant of the brassinosteroid receptor BRI1 and are defective in one of the Arabidopsis Htm1/EDEM homologs, AtEDEM1. We show that the wild-type AtEDEM1, but not its catalytically inactive mutant, rescues irb1-1. Importantly, an insertional mutation of the Arabidopsis Asparagine-Linked Glycosylation 3 (ALG3), which causes N-linked glycosylation with truncated glycans carrying a different free 1,6-mannose residue, completely nullifies the inhibitory effect of irb1-1 on bri1-5 ERAD. Interestingly, an insertional mutation in AtEDEM2, the other Htm1/EDEM homolog, has no detectable effect on bri1-5 ERAD; however, it enhances the inhibitory effect of irb1-1 on bri1-5 degradation. Moreover, AtEDEM2 transgenes rescued the irb1-1 mutation with lower efficacy than AtEDEM1. Simultaneous elimination of AtEDEM1 and AtEDEM2 completely blocks generation of 1,6-mannose-exposed N-glycans on bri1-5, while overexpression of either AtEDEM1 or AtEDEM2 stimulates bri1-5 ERAD and enhances the bri1-5 dwarfism. We concluded that, despite its functional redundancy with AtEDEM2, AtEDEM1 plays a predominant role in promoting bri1-5 degradation.